White Light Photothermal Lens Spectrophotometer for the Determination of Absorption in Scattering Samples. Issue 6 (June 2014) - Marcano, Aristides; Alvarado, Salvador; Meng, Junwei; Caballero, Daniel; Moares, Ernesto Marín; Edziah, Raymond
We developed a pump-probe photothermal lens spectrophotometer that uses a broadband arc-lamp and a set of interference filters to provide tunable, nearly monochromatic radiation between 370 and 730 nm as the pump light source. This light is focused onto an absorbing sample, generating a photothermal lens of millimeter dimensions. A highly collimated monochromatic probe light from a low-power He–Ne laser interrogates the generated lens, yielding a photothermal signal proportional to the absorption of light. We measure the absorption spectra of scattering dye solutions using the device. We show that the spectra are not affected by the presence of scattering, confirming that the method only measures the absorption of light that results in generation of heat. By comparing the photothermal spectra with the usual absorption spectra determined using commercial transmission spectrophotometers, we estimate the quantum yield of scattering of the sample. We discuss applications of the device for spectroscopic characterization of samples such as blood and gold nanoparticles that exhibit a complex behavior upon interaction with light.